Effects of adjunctive pimavanserin and current antipsychotic treatment on QT interval prolongation in patients with schizophrenia - Bugarski-Kirola, Dragana; Nunez, Rene; Odetalla, Ramzey; Liu, I-Yuan; Turner, Mary Ellen (Frontiers in Psychiatry, 2022)
Background Pimavanserin prolongs the QT interval, with mean increases in corrected QT (QTc) of 5–8 ms, and is currently being investigated for the treatment of negative symptoms of schizophrenia. Objectives To assess QT interval prolongation in 3 studies investigating once-daily pimavanserin as an adjunct to current antipsychotic treatment in patients with schizophrenia. Methods Electrocardiograms were unblinded from trials in which pimavanserin or placebo was added to main antipsychotics over 6 weeks (ENHANCE), 26 weeks (ADVANCE), and up to 78 weeks (ongoing 52-week, open-label extension study [study 035]) of treatment. Antipsychotic treatment was permitted throughout these studies. The 3 most frequently used antipsychotic treatments were examined—aripiprazole (including long-acting injectable), risperidone (including long-acting injectable), and olanzapine. QT intervals were corrected (QTc) using Fridericia's method, with elevated risk defined as either postbaseline value maximum of >500 ms or change from baseline to postbaseline maximum of >60 ms. Results Of patients treated with adjunctive pimavanserin in ENHANCE, there were no postbaseline QTc values >481 ms; one patient in each of the risperidone and aripiprazole groups had change from baseline to postbaseline maximum >60 ms. More patients had change from baseline to postbaseline maximum ranging from 31 to 60 ms in the risperidone plus adjunctive placebo group (n = 5; 6.6%) than those in the risperidone plus adjunctive pimavanserin group (n = 3, 4.1%). In the pimavanserin plus antipsychotic group of ADVANCE, one patient had postbaseline QTc value >481 ms, and one patient treated with aripiprazole had change from baseline to postbaseline maximum of >60 ms. In study 035, a change from double-blind baseline to overall postbaseline maximum >60 ms occurred in one patient treated with aripiprazole and pimavanserin and in one patient treated with risperidone and pimavanserin. Similar proportions of patients had changes from double-blind baseline to post double-blind baseline maximum between 31 and 60 ms across treatments. No adverse events associated with an increase in the QTc interval were reported. Conclusions Adjunctive pimavanserin with background antipsychotic treatment showed no evidence of QTc prolongation >500 ms postbaseline, consistent with previously reports on QT prolongation with pimavanserin.